The Influence of Virtual Streamers on Consumer Purchase Intention in Shopee Live Streaming in the Fashion Segment - Safina Dhany Alveria; Hanifa Nur Fadhilla (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study examines the influence of virtual streamer characteristics on consumer purchase intention in Shopee Live’s fashion segment in Indonesia, addressing the limited empirical evidence on virtual influencers in live commerce contexts. While prior studies predominantly focus on human streamers or general social media influencers, this research offers novel insights by investigating virtual streamers as emerging digital marketing agents in live shopping environments. Using a quantitative approach, data were collected from 150 consumers in the Special Region of Yogyakarta through purposive sampling and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results reveal that likeability does not directly affect purchase intention, indicating that consumers prioritize functional factors such as product attributes, pricing, and promotional incentives over streamer persona. However, likeability and responsiveness significantly enhance social presence, which in turn positively influences purchase intention. Responsiveness also shows a direct positive effect on purchase intention, underscoring the importance of real-time interaction in live commerce. These findings contribute to the literature by clarifying the indirect role of virtual streamer attributes through social presence and offer practical implications for fashion brands to optimize interactive strategies and engagement-driven content when deploying virtual streamers in live shopping platforms.